Nangibotide in patients with septic shock: a Phase 2a randomized controlled clinical trial - François, Bruno; Wittebole, Xavier; Ferrer, Ricard; Mira, Jean-Paul; Dugernier, Thierry; Gibot, Sébastien; Derive, Marc; Olivier, Aurélie; Cuvier, Valérie; Witte, Stephan; Pickkers, Peter; Vandenhende, François; et al. (Intensive care medicine, 2020)
Purpose Nangibotide is a specific TREM-1 inhibitor that tempered deleterious host–pathogens interactions, restored vascular function, and improved survival, in animal septic shock models. This study evaluated the safety and pharmacokinetics of nangibotide and its effects on clinical and pharmacodynamic parameters in septic shock patients. Methods This was a multicenter randomized, double-blind, two-stage study. Patients received either continuous infusion of nangibotide (0.3, 1.0, or 3.0 mg/kg/h) or placebo. Treatment began < 24 h after shock onset and continued for up to 5 days. Safety primary outcomes were adverse events (AEs), whether serious or not, and death. Exploratory endpoints evaluated nangibotide effects on pharmacodynamics, organ function, and mortality, and were analyzed according to baseline sTREM-1 concentrations. Results Forty-nine patients were randomized. All treatment emergent AEs (TEAEs) were collected until Day 28. No significant differences were observed in TEAEs between treatment groups. No drug withdrawal linked to TEAE nor appearance of anti-drug antibodies were reported. Nangibotide pharmacokinetics appeared to be dose-proportional and clearance was dose-independent. Nangibotide did not significantly affect pharmacodynamic markers. Decrease in SOFA score LS mean change (± SE) from baseline to Day 5 in pooled nangibotide groups versus placebo was − 0.7 (± 0.85) in the randomized population and − 1.5 (± 1.12) in patients with high baseline plasma sTREM-1 concentrations (non-significant). This pattern was similar to organ support end points. Conclusion No significant increases in TEAEs were detected in nangibotide-treated patients versus placebo. These results encourage further evaluation of nangibotide and further exploration of plasma sTREM-1 concentrations as a predictive efficacy biomarker.